Private Health Sector Assessment in Tanzania - White, James; O’Hanlon, Barbara; Chee, Grace; Malangalila, Emmanuel; Kimambo, Adeline; Coarasa, Jorge; Callahan, Sean; Levey, Ilana Ron; McKeon, Kim (Washington, DC: World Bank, 2013)
Tanzania exemplifies the developing world's struggle to achieve 'middle-income' country status while confronting widespread poverty and substantial health challenges-such as persistently high child and maternal mortality, human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS), tuberculosis (TB), and malaria. In this context, Tanzania's National Public Private Partnership (PPP) policy and second Health Sector Strategic Plan (HSSP) included a call for a private health sector assessment. Accordingly, following a regional technical exchange in Mombasa, Kenya, Tanzania's PPP Technical Working Group (TWG) requested that the Health in Africa (HIA) initiative of the International Finance Corporation (IFC) conduct an assessment of the private health sector in mainland Tanzania. Given a history of collaboration between HIA and the USAID-funded project Strengthening Health Outcomes through the Private Sector (SHOPS), which has included holding regional technical workshops on private sector engagement that have drawn representatives from over 14 African countries, HIA engaged SHOPS to lead the effort. With funding support from HIA and the USAID Office of HIV/AIDS, SHOPS assembled a nine-person assessment team composed of health system experts from IFC, SHOPS, USAID, and local stakeholder organizations. The broad focus of the assessment was the status of existing PPPs within the Tanzanian health system, with specific attention also to the opportunities for operationalizing improved private health sector engagement in the key health areas of HIV/AIDS, malaria, TB, and reproductive and child health (RCH)-specifically related to the policy-making process, health financing, and service delivery. The final section of the report presents strategic priorities that aim to assist the GOT and PPP-TWG in strategically engaging the private health sector for rapid health gains and more long-term sustainable health system reform. By seizing existing partnership opportunities and fostering a health system that leverages the skills, resources, and talents of all health actors, the goal of delivering accessible and high-quality health care to all Tanzanians is achievable.